2003
DOI: 10.1001/jama.289.12.1523
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lead, Blood Pressure, and Hypertension in Perimenopausal and Postmenopausal Women

Abstract: ContextLead exposures have been shown to be associated with increased blood pressure and risk of hypertension in older men. In perimenopausal women, skeletal lead stores are an important source of endogenous lead exposure due to increased bone demineralization.ObjectiveTo examine the relationship of blood lead level with blood pressure and hypertension prevalence in a population-based sample of perimenopausal and postmenopausal women in the United States.Design, Setting, and ParticipantsCross-sectional sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
1
4

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(126 citation statements)
references
References 63 publications
7
114
1
4
Order By: Relevance
“…Results of studies of adults with either occupational or environmental lead exposure have shown consistent associations between increased BLLs and increased blood pressure (Nash et al, 2003;Schwartz, 1995;Staessen et al, 1995) and associations between increased bone lead concentrations and blood pressure Korrick et al, 1999). High dose occupational lead exposure, usually with BLLs greater than 40 mg/dL, may alter sperm morphology, reduce sperm count, and decrease fertility (Alexander et al, 1996;Telisman et al, 2000).…”
Section: Urinary Lead (Creatinine Corrected)mentioning
confidence: 97%
See 1 more Smart Citation
“…Results of studies of adults with either occupational or environmental lead exposure have shown consistent associations between increased BLLs and increased blood pressure (Nash et al, 2003;Schwartz, 1995;Staessen et al, 1995) and associations between increased bone lead concentrations and blood pressure Korrick et al, 1999). High dose occupational lead exposure, usually with BLLs greater than 40 mg/dL, may alter sperm morphology, reduce sperm count, and decrease fertility (Alexander et al, 1996;Telisman et al, 2000).…”
Section: Urinary Lead (Creatinine Corrected)mentioning
confidence: 97%
“…BLLs and associated toxic effects differ in children and adults. For instance, BLLs near 10 µg/dL can affect blood pressure in adults and neurodevelopment in children (Bellinger, 2004;CDC, 1991;Nash et al, 2003;Schwartz, 1995;Staessen et al, 1995). In 1991, based on prospective population studies, the Centers for Disease Control and Prevention (CDC) established a BLL of 10…”
Section: Urinary Leadmentioning
confidence: 99%
“…Although many studies have explored the association between higher lead burdens and hypertension in adult males (Nawrot et al, 2002) and, to a lesser extent, adult females (Nash et al, 2003), few have focused specifically on hypertension during pregnancy. An early report suggested such a link (Rabinowitz et al, 1987), although in that study umbilical cord blood lead level was the sole exposure biomarker measured, and pregnancy hypertension was identified using obstetrical records rather than by direct measurement of blood pressure or assessment of clinical status.…”
Section: Pregnancy Hypertensionmentioning
confidence: 99%
“…Vupputuri et al, [22] showed that significant associations between blood lead level and systolic and diastolic blood pressures in black men. Nash et al, [17] found that B-Pb level is positively associated with both systolic and diastolic blood pressure in postmenopausal women. Recently, Kasperczyk et al, [29] found that B-Pb levels were positively correlated with high arterial blood pressure (both systolic and diastolic).…”
Section: Discussionmentioning
confidence: 99%
“…We used the mean of three systolic and diastolic blood pressure measurements, all of which were taken by a physician in the Clinical Unit of Qassim University. Patients were categorized as hypertensive if any of the following criteria were met: current user of blood pressure medication (self-report), a systolic blood pressure of 140 mm Hg or higher, or a diastolic blood pressure of 90 mm Hg or higher [17].…”
Section: Methodsmentioning
confidence: 99%